The Multidisciplinary Management of Fused Maxillary Lateral Incisor with a Supernumerary Tooth in Cleft Lip Adolescence - Ahmet Yagci; Kenan Cantekin; Suleyman Kutalmis Buyuk; Kansad Pala (Case Reports in Dentistry)
Fusion, an uncommon anomaly of the hard dental tissues, is potentially the cause of clinical problems related to esthetics, tooth spacing, and other periodontal complications. This paper describes a multidisciplinary approach involving surgical, endodontic, restorative, and orthodontic attention for the successful, functional, and esthetic rehabilitation of a maxillary left lateral incisor fused with a supernumerary tooth in unilateral cleft lip adolescence in contralateral side. After clinical and radiographic examinations, a fusion between the left maxillary lateral incisor and a supernumerary tooth was diagnosed in the patient, and a small connection was detected between the pulp systems of the two root canals. The case reported in this paper presents the successful resolution of a fused maxillary lateral incisor with a supernumerary tooth, using endodontic, surgical, restorative, and orthodontic management. The decision made in extracting or retaining the fused tooth depends on the arch discrepancy and esthetic needs. Future studies, with long-term followup, will be helpful in evaluating the long-term efficacy of the different treatment options.